Steuermehreinnahmen eröffnen budgetäre Spielräume zum Abbau der kalten Progression - Heinz Gebhardt (Wirtschaftsdienst, 2012)
Der Arbeitskreis Steuerschätzungen hat seine Prognose für das Steueraufkommen abermals nach oben revidiert. Damit können Bund, Länder und Kommunen bis 2016 mit höheren Steuereinnahmen rechnen, als bislang erwartet. Die Mehreinnahmen eröffnen budgetäre Handlungsspielräume, um die kalte Progression abzubauen, wenn gleichzeitig sparsam gewirtschaftet wird. – – In May 2012 the Working Party on Tax Revenue Forecasting released a tax revenue estimate for the current year and the following four years based on key macroeconomic data supplied by the German Federal Government. The new offi cial tax estimate forecasts additional revenues for central, state and local government. Tax revenues are expected to bring additional exteuro24.9bn between 2012 and 2016. With the budgetary leeway, the fi scal drag, which has occurred since 2010, could be eliminated in 2013 and 2014. The Act to reduce fi scal drag would result in a revenue loss of exteuro6bn a year.
Keywords: H20; H62; H71; 330; Steueraufkommen; Steuerprogression; Steuersenkung; Deutschland